Careers in Mental Health - Assistance and Referral Centre (ARC) (2019)

Academic Year 2018-2019 : Health and Social Services Community Leadership Bursary Program - Dialogue McGill (2019)

Impact of the 2011-2014 Community Leadership Bursary Program : Adjustments for the future? - Gagnon, Marie-Pierre; Lampron, Amélie (2018)

Année scolaire 2017-2018 : Programme de bourses de leadership communautaire en santé et services sociaux - Dialogue McGill (2018)

Programme de maintien en poste : Monitoring des stagiaires - Storr, Caroline; Hendrickson, Mary (2018)

Retention Program : Monitoring of Internship Students - Storr, Caroline; Hendrickson, Mary (2018)

Health and Social Services Community Leadership Bursary Program : Annual report - Gagnon, Marie-Pierre; Lampron, Amélie (Dialogue McGill, 2017)
This document is the second annual report on the monitoring of the McGill Health and Social Services Community Leadership Bursary Program.1 It aims to present data related to bursaries awarded for the 2014-2017 period, based on data collected during the 2016-2017 academic year, outlining their distribution by region and other variables such as level of study, program of study, and recipients’ medium-term intentions. The report also provides a profile of graduate recipients for whom post- graduation follow-up was required during the period covered. Since this is not a research or evaluation report, data presented in the report are merely descriptive.

Health and Social Services Community Leadership Bursary Program : Bi-annual report - Gagnon, Marie-Pierre; Lampron, Amélie (Dialogue McGill, 2017)
This document is the third bi-annual report on the monitoring of the McGill Health and Social Services Community Leadership Bursary Program. This report aims to present data related to bursaries awarded for the 2014-2017 period, taking into account the recipients’ situation as of the second semester of the 2016-2017 academic year, outlining their distribution by region and other variables such as level of study, program of study, and recipients’ medium-term intentions. Since this is not a research or evaluation report, data presented in the report are merely descriptive.

Programme de bourses de leadership communautaire en santé : rapport semestriel - Gagnon, Marie-Pierre; Lampron, Amélie (Dialogue McGill, 2017)
Ce document constitue le troisième rapport semestriel réalisé dans le cadre du projet d’implantation du mécanisme de suivi du programme de bourses de leadership communautaire en santé et en services sociaux de McGill. Le présent rapport a pour objectif de présenter les données relatives aux bourses octroyées aux boursiers du programme de bourses couvrant la période 2014-2017, en faisant état de la situation en date du second semestre de l’année scolaire 2016-2017, en dressant notamment un portrait de leur répartition selon les régions et autres variables telles que le niveau de scolarité, le programme d’étude et les intentions à moyen terme des récipiendaires. Ne s’agissant pas d’un rapport de recherche ou d’évaluation, les données présentées dans ce rapport sont essentiellement de nature descriptive.

Health and Social Services Community Leadership Bursary Program : Bi-annual report fall 2016 - Gagnon, Marie-Pierre; Lampron, Amélie (Dialogue McGill, 2016)
This document is the second annual report on the monitoring of the McGill Health and Social Services Community Leadership Bursary Program.1 It aims to present data related to bursaries awarded for the 2014-2017 period, based on data collected during the 2016-2017 academic year, outlining their distribution by region and other variables such as level of study, program of study, and recipients’ medium-term intentions. The report also provides a profile of graduate recipients for whom post- graduation follow-up was required during the period covered. Since this is not a research or evaluation report, data presented in the report are merely descriptive.

Programme de bourses de leadership communautaire en santé : rapport semestriel automne 2016 - Gagnon, Marie-Pierre; Lampron, Amélie (Dialogue McGill, 2016)
Ce document constitue le second rapport semestriel réalisé dans le cadre du projet d’implantation du mécanisme de suivi du programme de bourses de leadership communautaire en santé et en services sociaux de McGill. Le présent rapport a pour objectif de présenter les données relatives aux bourses octroyées aux boursiers du programme de bourses couvrant la période 2014-2017, en faisant état de la situation en date du premier semestre de l’année scolaire 2016-2017. Les données recueillies permettent notamment de dresser un portrait de leur répartition selon les régions et autres variables telles que le niveau de scolarité, le programme d’étude et les intentions à moyen terme des récipiendaires. Ne s’agissant pas d’un rapport de recherche ou d’évaluation, les données présentées dans ce rapport sont essentiellement de nature descriptive.

The McGill Retention Bursary Program: Evaluation Report : Training and Retention of Health Professionals Project - Gagnon, Marie-Pierre; Lampron, Amélie (CHU de Québec Research Centre, 2015)
An evaluation of this bursary program was conducted, focusing on the components of the program (e.g. eligibility criteria, selection process, etc.) and its outcomes (e.g. recipient intention to return to or stay working in a selected Quebec region at the end of their training, potential impact of the bursary program on retention of health professionals in English-speaking communities, etc.). The objectives of the evaluation were 1) to describe the current processes related to the functioning of the McGill Retention Bursary Program; 2) to explore recipients’ experience of this bursary program; 3) to explore community networks’ experience regarding their collaboration with this bursary program; 4) to assess the effectiveness of the bursary program; and 5) to propose potential improvement strategies for the bursary program currently in place.